Performance Evaluation of IRIS and LOTUS Motes When Communicating in Real Environments - Mohammed S. Habtoor; Hosam Rowaihy (International Journal of Distributed Sensor Networks)
Wireless sensor network (WSN) technology has rapidly spread into many fields. Recently, this technology has come to the forefront among the scientific community. The usage of sensors and the possibilities of organizing them into networks have motivated several topics of research and have highlighted different means of addressing certain problems, of which one of the most important is communication. In this paper, we report a study of the communication performance of two generations of wireless motes (IRIS and LOTUS) in various real scenarios and environments. This study will assist decision-makers in choosing the most appropriate sensor technology for their specific applications and requirements.